Mixed-mode quadrature oscillator using a single DDCCTA and grounded passive components - Phatsornsiri, Punnavich; Lamun, Panit; Kumngern, Montree (My University, 2015)
A new mixed-mode quadrature oscillator using a single differential difference current conveyor transconductance amplifier (DDCCTA), two grounded resistors, and two grounded capacitors is presented. The proposed circuit provides both quadrature voltage and quadrature current outputs simultaneously. The condition of oscillation (CO) and frequency of oscillation (FO) of the circuit are orthogonally controllable. The circuit is beneficial to monolithic integrated circuit implementation by using all grounded passive components. Moreover, the active and passive sensitivities of the proposed configuration are low. The validity of the proposed oscillator has been established by PSPICE simulations using MIETEC 0.5 μm CMOS technology.
Keywords: differential difference current conveyor transconductance (DDCCTA); mixed-mode circuit; quadrature oscillator